Effective E-Learning Interface Design In Online Game: A Case Study Of The SIMS 2 - Zainal Abidin, Sazrinee (2007)
This research focuses on how effective e-Learning interface design could influence the learning process in online game. Researcher has chosen The Sims 2 as a case study. The Sims 2 is the world's most successful "artificial intelligence" and "people simulator" game.